O5.2. CBD MODULATION OF HIPPOCAMPAL GLUTAMATE IN PSYCHOSIS. (18th May 2020) - O'Neill, Aisling; Annibale, Luciano; Blest-Hopley, Grace; Wilson, Robin; Bhattacharyya, Sagnik
Abstract: Background: Emerging evidence supports the antipsychotic effect of cannabidiol (CBD), a non-intoxicating component of cannabis, in people with psychosis. However, how CBD might exert its antipsychotic effect remains unclear. While current antipsychotic medications typically target the dopaminergic neurotransmitter system, preclinical findings suggest that CBD may directly or indirectly affect multiple distinct modes of neural signalling, including both glutamate and dopamine. However, no study has as yet investigated the effect of CBD on brain glutamate levels in patients with psychosis as a potential mechanism underlying its antipsychotic effects. Methods: We investigated the effects of a single oral dose of CBD (600mg), compared to a matched placebo, in patients within 5 years of onset of psychosis, using a double-blind, randomized, placebo-controlled, repeated-measures, within-subject cross-over design, with at least a one-week interval between scans to allow washout of CBD. After drug administration, 13 patients (mean age 27.73, 66.7% male) were scanned using proton magnetic resonance spectroscopy to measure left hippocampal glutamate levels. Symptom severity was assessed using the Positive and Negative syndrome scale (PANSS) 60mins before drug administration (T1, pre scan), and 270mins after drug administration (T2, post scan). Effects of CBD on left hippocampal glutamate levels, symptoms, and correlations between hippocampal glutamate and symptoms were investigated. Results: Compared to placebo, there was a significant increase in left hippocampal glutamate in the psychosis patients under CBD treatment (z= -1.80; p=0.035). Under placebo treatment, change in positive psychotic symptoms (as indexed using the T1 minus T2 PANSS positive symptoms subscale scores) was directly correlated with left hippocampal glutamate levels (rho= 0.69, p=0.004), such that symptoms increased as hippocampal glutamate levels decreased. This significant relationship was not observed under the CBD treatment (rho= 0.102, p=0.72). Discussion: This suggests that positive psychotic symptoms may be driven by abnormal hippocampal glutamate concentration, which is sensitive to modulation by CBD. These findings are in keeping with the purported antipsychotic effects of CBD in psychosis, and provide novel insight into the neurochemical interactions underlying these effects.